저선량 감마선 반복조사의 육류와 생선 중 미생물 저감효과 - 제길수; 정덕화; 심원보; Je, Gil-Soo; Chung, Duck-Hwa; Shim, Won-Bo (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2015)
The aim of this study is to examine the removal efficiency of pathogen (Escherichia coli O157:H7 and Salmonella typhimurium) on meat and fish products (packing condition: vacuum or not and storage temperature: $4^{°}C$ or $-20^{°}C$) repeatedly exposed at low-dose gamma irradiation. In case of meat products (beef and chicken), E. coli O157:H7 was not observed at the level of 2 kGy single gamma irradiation and 0.5 kGy repeated gamma irradiation and S. Typhimurium was not observed at the level of 2 kGy single gamma irradiation and 1 kGy repeated gamma irradiation. In case of fish products, E. coli O157:H7 and S. Typhimurium were not detected at the level of 0.5 kGy single and repeated gamma irradiation. These results showed that microorganisms on fish products were more efficiently removed than those of meat products with low-dose gamma irradiation. Generally, each packing condition made no difference. However, the products (fish and meat) stored at $-20^{°}C$ needed more higher dose gamma irradiation than products at $4^{°}C$. 본 연구에서는 포장방법 (진공, 일반)과 저장온도($4^{°}C$, $-20^{°}C$)를 달리한 육류 (소고기, 닭고기) 및 생선에 대해 저선량 감마선 반복조사를 적용하였을 때 나타나는 병원성 미생물 E. coli O157:H7 및 S. Typhimurium의 사멸효과를 확인하였다. 소고기와 닭고기의 경우 E. coli O157:H7은 최소 2 kGy 이상의 단일조사와 0.5 kGy 이상으로 반복조사 시 생육이 확인되지 않았고, S. Typhimurium은 최소 2 kGy 이상의 단일조사와 1 kGy 이상으로 반복조사 시 생육이 확인되지 않았다. 생선의 경우 최소 0.5 kGy 이상의 단일 및 반복조사 시 E. coli O157:H7 와 S. Typhimurium의 생육이 확인되지 않았다. 육류보다 생선이 낮은 선량으로 미생물을 사멸시킬 수 있었으며, 전반적으로 포장 방법에 따른 조사선량의 차이는 없었으나 저장온도의 경우 냉장보다 냉동의 경우가 좀 더 높은 조사선량을 요구하는 것으로 확인되었다.